2015
DOI: 10.1021/jm501567f
|View full text |Cite
|
Sign up to set email alerts
|

Oleanane Triterpenes from the Flowers of Camellia japonica Inhibit Porcine Epidemic Diarrhea Virus (PEDV) Replication

Abstract: Porcine epidemic diarrhea virus (PEDV) infections have resulted in a severe economic loss in the swine industry in many countries due to no effective treatment approach. Fifteen oleanane triterpenes (1-15), including nine new ones (1-4 and 10-14), were isolated from the flowers of Camellia japonica, and their molecular structures were determined by extensive spectroscopic methods. These compounds were evaluated for their antiviral activity against PEDV replication, and the structure-activity relationships (SAR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
45
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 48 publications
1
45
1
1
Order By: Relevance
“…Previous studies showed that PR inhibited HIV-1 replication and human respiratory syncytial virus activities in vitro (20,21). Some medicinal herbal extracts, such as oleanane triterpenes from the flowers of Camellia japonica, Sophorae radix, Acanthopanacis cortex, Sanguisorbae radix, and Torilis fructus, can inhibit PEDV replication (49,50). To date, there is little information regarding an anti-PEDV effect of PR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies showed that PR inhibited HIV-1 replication and human respiratory syncytial virus activities in vitro (20,21). Some medicinal herbal extracts, such as oleanane triterpenes from the flowers of Camellia japonica, Sophorae radix, Acanthopanacis cortex, Sanguisorbae radix, and Torilis fructus, can inhibit PEDV replication (49,50). To date, there is little information regarding an anti-PEDV effect of PR.…”
Section: Discussionmentioning
confidence: 99%
“…Lin et al found that the water extract of Pueraria lobata Ohwi has anti-viral activity against human respiratory syncytial virus in human respiratory tract cell lines (21). Therefore, these results suggest that PR could Abbreviations: GBPs, guanylate-binding proteins; HPRT1, hypoxanthine phosphoribosyltransferase 1; IFIT3, interferon-induced protein 3; IL-1β, interleukin−1β; IL-8, interleukin-8; ISGs, interferon-stimulated genes; MCP-1, monocyte chemotactic protein 1; NF-κB, nuclear factor kappa-B; OAS1, 2 ′ -5 ′ oligoadenylate synthetase 1; PEDV, porcine epidemic diarrhea virus; PEDV-M, membrane protein (porcine epidemic diarrhea virus); PEDV-N, nucleocapsid protein (Porcine epidemic diarrhea virus); RPL4, ribosomal protein L4; TCID 50 , 50% tissue culture infectious dose; TNF-α, tumor necrosis factor α. be a promising supplement for antiviral therapy. However, little is known about its effectiveness against PEDV infection.…”
Section: Introductionmentioning
confidence: 99%
“…Vaccination is a fundamental strategy for controlling and eradicating PED during epidemic or endemic outbreaks, but the efficacy is limited (Baek et al, 2016;Shen et al, 2015). Until now there is no recorded clinically effective antiviral chemotherapeutic agent for treatment of disease caused by PEDV, even several compounds were demonstrated having antiviral activity in PEDV-infected Vero cells (Deejai et al, 2017;Yang et al, 2015;Lee et al, 2015;Kwon et al, 2013;Choi et al, 2009). So it is important to develop an effective strategy against PEDV infection.…”
Section: Discussionmentioning
confidence: 99%
“…To protect against PEDV infection, various prophylactics have been developed using Escherichia coli expressing PEDV neutral single chain variable fragments (Pyo et al, 2009), plant extracts (Choi et al, 2009;Lee et al, 2015;Yang et al, 2015), and chemicals such as antiviral drugs (Kim and Lee, 2013). Most studies have used African monkey kidney epithelial cell lines such as VeroE6 while PEDV targets the porcine cells.…”
Section: Introductionmentioning
confidence: 99%